A Highly Isolated Tapered Triangular Dual-Polarized Multiband MIMO Antenna for WLAN, C, X and Ku Bands - Sonali Kumari; Yogendra Kumar Awasthi; Dipali Bansal; Rohit Anand; Praveen Kumar Malik; Rajesh Singh (International Journal of Antennas and Propagation)
This research work presents the design of a multiband dual-polarized eight-element MIMO antenna having dimensions (0.51 λ × 0.66 λ × 0.009 λ). The antenna is observed to be radiating between 1.7 GHz and 2.4 GHz, 4.1 GHz and 10 GHz and 10.6 GHz and 19.8 GHz, featuring 3 dB axial ratio bandwidth between 9.7 and 10 GHz, 12.1 and 13.1 GHz, 14.4 and 14.5 GHz and 17.9 and 18.9 GHz. In the proposed MIMO antenna, the triangular-shaped monopole antenna is tapered at its two sides. The isolation between the various elements of the proposed antenna is observed to be in range of −20 dB–−70 dB for the concerned frequency range. On the basis of comparison with similar existing structures, the proposed antenna demonstrates superior performance in terms of total active reflection coefficient (TARC < −5 dB), diversity gain (DG around 10 dB), channel capacity loss (CCL < 0.3 bits/s/Hz), mean effective gain (MEG) and envelope correlation coefficient (ECC < 0.024). The proposed antenna provides wide bandwidth (15.8 GHz) and high value of peak gain (6 dB). The proposed geometry is novel as it exhibits both linear as well as circular polarization with multiband response and it provides the least ECC and maximum isolation. The experimental results are found to be in agreement with the simulated results, so the proposed antenna can be useful for WLAN, C-band, X band and Ku band applications.